2019
DOI: 10.1080/21691401.2019.1640708
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Bilobalide protects H9c2 cell from oxygen-glucose-deprivation-caused damage via upregulation of miR-27a

Abstract: Background: Myocardial ischemia is a troublesome disease. Bilobalide possesses multiple biological functions. We researched the consequents of bilobalide in OGD-irritated H9c2 cells. Methods: OGD-stimulated H9c2 cells were treated by bilobalide, and/or transfected with miR-27a inhibitor or negative control. Use CCK-8 and flow cytometry to test cell activity and apoptosis, respectively. Luciferase activity experiment was to test targeting link between miR-27a and Tmub1. Levels of cell-cycle and apoptosis relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Hua et al ( 51 ) revealed that BB could protect neural cells against aggregated α-synuclein-induced apoptosis. Cao and Li ( 52 ) observed that BB ameliorated OGD-induced injury in H9c2 cells. A study by Mao et al ( 53 ) demonstrated that BB alleviated IL-17-induced inflammatory injury in ATDC5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hua et al ( 51 ) revealed that BB could protect neural cells against aggregated α-synuclein-induced apoptosis. Cao and Li ( 52 ) observed that BB ameliorated OGD-induced injury in H9c2 cells. A study by Mao et al ( 53 ) demonstrated that BB alleviated IL-17-induced inflammatory injury in ATDC5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Post-transcriptional or post-translational regulation, such as 3′UTR modification, acetylation, or methylation may be involved; miR-449a-5p [ 43 ], miR-34a-5p [ 44 ], and miR-30b-5p [ 45 ] have been found to be responsible for SIRT1-targeted inhibition. BB regulates the expression of miRNAs such as miR-101-5p and miR-27a-5p, which have multiple biological functions [ 46 ]. Synthetically, Both AMPK and SIRT1 are energy-sensing molecules that have coexisted in cells throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…MI may cause perioperative ischemia and infarction (Pagliaro, Cannata, Stefanini, & Bolognese, 2020; Smit, Coetzee, & Lochner, 2020). Cao and Li (2019) established myocardial ischemic injury employing oxygen–glucose deprivation (OGD) and studied the role and mechanism of BB in OGD‐induced damage to rat myocardial H9c2 cells. It was found that BB can upregulate miR‐27a, activate PI3K/Akt and Wnt/β‐catenin signaling pathways, reduce the damage of H9c2 cells caused by OGD, improve cell viability, and reduce cell apoptosis to relieve MI.…”
Section: Pharmacological Effects Of Bbmentioning
confidence: 99%